GTV delineating for patients with postoperative glioma based on enhanced T2-FLAIR sequence instead of enhanced T1-TFE sequence: a feasibility study - Yuanyuan Li; Qingqing Yuan; Hengbing Jiang; Yin Zhang; Xingru Sun (Discover Oncology)
Abstract Objective To investigate the comparison of MRI Enhanced T2-Fluid Attenuated Inversion Recovery(T2-FLAIR+C) sequence and Enhanced T1-Turbo Field Echo(T1-TFE+C) sequence in delineating Gross Tumor Volume (GTV) of postoperative glioma. Method Twenty patients with postoperative glioma underwent MRI simulation(MRI-sim) were enrolled. The T1-TFE+C sequence and T2-FLAIR+C sequence were separately registered with CT simulation(CT-sim). GTV was delineated by the same physician based on CT/T1 and CT/T2, respectively. Subsequently, the number, volume and overlapping ratio(OR) of GTV between the two groups were quantified and analyzed statistically. The signal intensity(SI) of the tumor area, normal gray matter and white matter (background of normal brain tissue)were measured on T1-TFE+C and T2-FLAIR+C sequences, respectively. The contrast ratio(CR) of the tumor in the two sequences were calculated and statistically analyzed. Results The volumes of GTV delineated based on CT/T1 and CT/T2 were (55.89 ± 30.20) cm3 and (56.75 ± 30.52) cm3, respectively. There was no statistically significance between the two groups of GTV volumes (P > 0.05). The maximum OR, minimum OR and average OR of GTV volumes between the two groups were 99.77%, 86.90%, and 94.51%, respectively. The CR of tumor/white matter and tumor/gray matter in T2-FLAIR+C were significantly higher than those in the T1-TFE+C sequence (P < 0.05). Conclusion The volume of GTV delineated by T2-FLAIR+C was slightly larger compared to that by T1-TFE+C, and T2-FLAIR+C could provide a more comprehensive range of GTV delineation. CR was statistically significant between the two groups (P < 0.05), and T2-FLAIR+C demonstrated the ability to accurately depict changes in tumor boundaries and surrounding edema with a higher tumor enhancement signal. Therefore, GTV delineation of gliomas based on T2-FLAIR+C may offer certain advantages and could potentially serve as a complete replacement for T1-TFE+C in future clinical applications.